Mechanized Margin to Digitized Center: Black Feminism's Contributions to Combatting Erasure within the Digital Humanities. Issue 1 (March 2016) - Brown, Nicole M.; Mendenhall, Ruby; Black, Michael L.; Moer, Mark Van; Zerai, Assata; Flynn, Karen
Abstract : Computational analysis and digital humanities are far from neutral processes and sites unimpeded by the political, social and economic context in which they emerged and are utilized. As an interdisciplinary field, the digital humanities have transformed the relationship of humans to computers broadly conceived. At the same time, the methods, theories, perspectives and the concomitant digital tools developed are being criticized for reproducing the social divisions that exist in society. The effort to recover Black women's subjectivities from the digital minefield is not without its challenges, reflected in our study which searched approximately 800, 000 books, newspapers, and articles in the HathiTrust and JSTOR Digital Libraries. The goal was to identify perceptions and lived experiences of Black women that emerged and the resulting knowledge that developed. The project team discovered multiple challenges related to the rescue and recovery of Black women's standpoints or group knowledge. This essay explores how even as computational analysis has embedded biases, it can be utilized to recover the experiences of Black women from within the digitized record. Thus, computational analysis and all that it encompasses not only makes visible Black women's experiences, but also expands the scope of the digital humanities.